THERMAL CONTROL OF ROLLING BEARINGS AT THE CANNING FACTORY - Перетяка, Наталья (SWorldJournal, 2021)
The paper considers the problems of thermal passive control of mechanical components. Methods of equipment maintenance at the enterprise are shown. The expedient method of non-destructive testing of rolling bearings of different types used in the technol